Young healthy adults with a family history of hypertension have increased microvascular reactivity but decreased macrovascular function. (20th January 2021) - Matthews, Evan L.; Guers, John J.; Hosick, Peter A.
Abstract: Objective: To determine whether, like hypertensives, normotensive adults with a family history of hypertension (+FHH) display lower microvascular reactivity and conduit artery function than normotensive adults without a family history of hypertension (−FHH). Methods: A forearm vascular occlusion test was performed on healthy normotensive adults while resting in the supine position. A near‐infrared spectroscopy sensor placed on the forearm measured skeletal muscle oxygen saturation kinetics to determine microvascular reactivity. Simultaneously, an ultrasound probe placed on the brachial artery above the occlusion cuff was used to assess flow‐mediated dilation; a test of macrovascular function. Results: Twenty‐two participants were included in this investigation (−FHH n = 13, +FHH n = 9). Following cuff release, the resaturation slope (1st 10 s median ± SD, −FHH 2.76 ± 2.10, +FHH 5.59 ± 2.47%/s; p = .036) was greater in +FHH when accounting for the magnitude and rate of the decrease in skeletal muscle oxygen saturation during occlusion. Conversely, flow‐mediated dilation (median ± SD, −FHH 5.96 ± 5.22, +FHH 4.10 ± 3.17%∆; p = .031) was lower in +FHH when accounting for baseline artery diameter and shear rate. Conclusions: Young +FHH adults have altered microvascular and macrovascular reactivity compared with young −FHH adults.